Estimación de la edad en que las hembras de anguila (A. anguilla) de la Albufera de Valencia realizan su migración reproductiva - Asturiano, JF; Mazzeo, I; Gallego, V; Heinsbroek, L; Pérez, L; Capoccioni, F.; CICCOTTI, ELEONORA (country:ES, 2011)
ONE-HUNDRED AND TWENTY EUROPEAN EEL FEMALES WERE CAPTURED IN THEIR REPRODUCTIVE MIGRATION FROM THE ALBUFERA LAGOON (VALENCIA, SPAIN). OTOLITHS WERE EXTRACTED AND PROCESSED, AND MEAN FEMALES AGE, 9.09±0.17 YEARS, WAS DETERMINED BY COUNTING ANNUAL OTOLITH RINGS. FEMALES SHOWED MORPHOMETRIC PARAMETERS SIMILAR TO THOSE DESCRIBED IN MIGRATORY FISH FROM OTHER POPULATIONS. ALBUFERA EELS SHOWED A HIGHER GROWTH RATE THAN OTHER POPULATIONS FROM THE NORTH OF EUROPE. THIS KIND OF RESULTS MUST BE CONSIDERED FOR THE ESTABLISHMENT OF MANAGEMENT PLANS OF THIS SPECIES.